Pathogenesis and Rehabilitation Therapy of Sleep Disorder after Stroke - HAN Xu; XIE Hongyu; TANG Xinwei; WU Yi (康复学报)
Sleep disorder after stroke are classified into sleep-disordered breathing (SDB), insomnia, excessive daytime sleepiness (EDS) and restless legs syndrome (RLS), which have a great impact on the prognosis of cognitive and motor functions and the quality of life of stroke patients. Rehabilitation treatment for sleep disorder in stroke patients should be initiated as early as possible. This study provides an overview of the pathogenesis and rehabilitation treatment of sleep disorder after stroke. The pathogenesis research of post-stroke sleep disorder mainly includes the pathogenesis of SDB [obstructive sleep apnea syndrome (OSAS), central sleep apnea syndrome (CSAS) and mixed sleep apnea syndrome (MSAS)], insomnia, EDS and RLS. Research on rehabilitation treatments for post-stroke sleep disorder mainly includes rehabilitation treatments for SDB [continuous positive airway pressure (CPAP), body positioning therapy, and oropharyngeal muscle training], insomnia [cognitive behavioral therapy (CBT), acupuncture, non-invasive transcranial neuromodulation techniques (low-frequency repetitive transcranial magnetic stimulation and transcranial direct current stimulation), and light therapy], EDS (CPAP and light therapy) and RLS (acupuncture). However, the pathogenesis of post-stroke sleep disorder is not yet fully clarified, and its basic research is still at the phenotypic determination stage. Issues such as treatment compliance, safety, and accuracy remain in rehabilitation treatment, and there is limited research on the rehabilitation of post-stroke EDS and RLS. Future explorations are needed on experimental animal models suitable for the basic research on post-stroke sleep disorder. In addition, more high-quality, large-sample, multicenter clinical randomized controlled trials are needed to provide references for the rehabilitation treatment of post-stroke sleep disorder.